Impact of the COVID-19 pandemic on the economic development of the mining and construction industry: Case study in Slovakia - Beátka Stehlíková; Marcela Taušová; Katarína Čulková (Economies, 2024)
Due to the present worldwide economic development, there is an increasing need to follow the financial health of companies in individual sectors to avoid possible decline and bankruptcy. The goal of this contribution is to find out the influence of the pandemic on the economic situation in the mining industry as the primary sector, in connection with the construction industry as the secondary sector. The research is carried out through economic and financial indicators, which mostly influence the potential crisis of companies. The results show that the mining industry and construction sectors managed to avoid the heavy decline and bankruptcy of certain organizations in the industries. Such results can be used for forecasting and modeling the socio-economic development of regions and countries. The growth of the analyzed industries could contribute to the sustainable development in the country.
Keywords: 330; economic indicators; financial health; primary and secondary sector; Slovakia